2015
DOI: 10.3390/brainsci5020220
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Behavioral Outcomes Following Temperature Modulation During Induced Neonatal Hypoxic Ischemic Injury in Rats

Abstract: Neonatal hypoxia ischemia (HI; reduced oxygen and/or blood flow to the brain) can cause various degrees of tissue damage, as well as subsequent cognitive/behavioral deficits such as motor, learning/memory, and auditory impairments. These outcomes frequently result from cardiovascular and/or respiratory events observed in premature infants. Data suggests that there is a sex difference in HI outcome, with males being more adversely affected relative to comparably injured females. Brain/body temperature may play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 98 publications
8
55
0
Order By: Relevance
“…We are the first to examine synaptic plasticity following therapeutic hypothermia after global ischemia. Given that learning induces LTP in behavior studies (Bliss and Collingridge, 1993; Bliss et al, 2006; Cooke and Bliss, 2006; Pastalkova et al, 2006; Whitlock et al, 2006), our data are consistent with prior observation that hypothermia preserves learning tasks after global ischemia (Colbourne and Corbett, 1995; Wagner et al, 2002; Smith et al, 2015). The impairment in LTP likely correlates with multiple observations that memory deficits are present following human CA (Grubb et al, 1996; Drysdale et al, 2000; O’Reilly et al, 2003; Sulzgruber et al, 2014), and animal ischemia (Kofler et al, 2004; Allen et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We are the first to examine synaptic plasticity following therapeutic hypothermia after global ischemia. Given that learning induces LTP in behavior studies (Bliss and Collingridge, 1993; Bliss et al, 2006; Cooke and Bliss, 2006; Pastalkova et al, 2006; Whitlock et al, 2006), our data are consistent with prior observation that hypothermia preserves learning tasks after global ischemia (Colbourne and Corbett, 1995; Wagner et al, 2002; Smith et al, 2015). The impairment in LTP likely correlates with multiple observations that memory deficits are present following human CA (Grubb et al, 1996; Drysdale et al, 2000; O’Reilly et al, 2003; Sulzgruber et al, 2014), and animal ischemia (Kofler et al, 2004; Allen et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…This may be particularly important in light of recent human studies showing lack of effect of hypothermia after out-of-hospital CA in children (Moler et al, 2015), suggesting a need for a better understanding through basic science. Further, it was also somewhat unexpected that there was a difference in the response to hypothermia in male and female juvenile mice, though questions regarding the depth of hypothermia have recently emerged from human trials (Nielsen et al, 2013) and previous reports have suggested sexually dimorphic responses in some behavior tasks in neonatal hypoxia–ischemia models (Burnsed et al, 2015; Smith et al, 2015). Lee and colleagues found that exposing neonatal male rats to 30 °C or 33 °C for varying lengths of time did not further reduce the loss of residual brain volume or motor behavior tasks one month after a model of neonatal hypoxic injury (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Results from the present study show that treated (IAIPs) and untreated HI injured rats maintain intact pre-pulse inhibition as compared to sham subjects as evidenced by comparable attenuation performance on the normal single tone detection task. These findings reflect those of other studies showing intact startle reactivity and basic hearing function in rats that have been exposed to HI brain injury as neonates (McClure, Peiffer et al 2005, McClure, Threlkeld et al 2006, Smith, Garbus et al 2015). Likewise, regardless of treatment, HI injured subjects were able to discriminate both short (0–10 ms) and long (0–100 ms) duration silent gaps embedded in white noise at levels comparable to sham subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Sexual dimorphism documented in preclinical models of HI may contribute to the variable injury and response to treatment [19,2124]. However, the importance of sex as a biological variable influencing HIE outcomes has been sparsely studied in humans [2527].…”
Section: Introductionmentioning
confidence: 99%